Team players and helpers – describing professional identity among finnish physicians in a cross-sectional study - Pyry Mattila; Harri Hyppölä; Teppo Heikkilä; Sami Heistaro; Minna Kaila; Petri Kulmala; Markku Sumanen; Pekka Mäntyselkä (BMC Medical Education, 2024)
Abstract Background Every physician has a unique professional identity. However, little is known about the diversity of identities among physicians. This study aimed to quantitatively assess the professional identity of physicians in Finland using descriptions of professional identity. Methods This study was part of a larger cross-sectional Finnish Physician 2018 Study. The target population consisted of all Finnish physicians under the age of 70 (N = 24,827) in 2018. The sample was drawn from physicians born on even numbered days (N = 11,336) using the Finnish Medical Association register. A total of 5,187 (46%) physicians responded. Professional identity was examined by 27 given characterisations using a five-point Likert scale. Multivariate logistic regression was used in assessing how place of work, graduation year and gender were associated with identity descriptions. Results The descriptions which most physicians identified with were “member of a working group/team” (82%), “helper” (82%), and “health expert” (79%); the majority reported these as describing them very or quite well. Identity descriptions such as “prescriber of medications” (68% vs. 45%), “prioritiser” (57% vs. 35%) and “someone issuing certificates” (52% vs. 32%) were more popular among junior than senior physicians. The biggest differences between the genders were found in the descriptions “provider of comfort” (62% vs. 40%) and “someone engaged in social work” (45% vs. 25%), with which women identified more frequently than men. Conclusions Strong identification as a member of a team is an important finding in the increasingly multiprofessional world of health care. Importantly, most physicians shared several core professional identity descriptions (i.e., helper, health expert) that reflect the traditional image of an exemplary doctor.